2018
DOI: 10.1155/2018/5236267
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Triiodothyronine Level with In-Hospital Cardiac Function and Long-Term Prognosis in Patients with Acute Myocardial Infarction

Abstract: Objective The pathophysiologic mechanism of how thyroid function is related to the development and prognosis of acute myocardial infarction (AMI) remains under explored, and there has been a lack of clinical investigations. In this study, we investigate the relationship between triiodothyronine (T3) level and cardiac ejection fraction (EF) as well as probrain natriuretic peptide (NT-proBNP) on admission and subsequent prognosis in AMI patients. Methods We measured admission thyroid function, NT-proBNP, and EF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…After a careful survey of the clinical literature, a strong inverse correlation between serum BNP and T3 in cardiac patients was noted in most studies (Bunevicius et al, 2006;Mayer et al, 2008;Pfister et al, 2010;Du et al, 2012;Brozaitiene et al, 2016;She et al, 2018;Sato et al, 2019). Indeed, the clinical literature spurred us to conduct the animal studies reported herein to confirm this inverse relationship.…”
Section: Bnp and T3 Treatment Of Hfmentioning
confidence: 55%
See 1 more Smart Citation
“…After a careful survey of the clinical literature, a strong inverse correlation between serum BNP and T3 in cardiac patients was noted in most studies (Bunevicius et al, 2006;Mayer et al, 2008;Pfister et al, 2010;Du et al, 2012;Brozaitiene et al, 2016;She et al, 2018;Sato et al, 2019). Indeed, the clinical literature spurred us to conduct the animal studies reported herein to confirm this inverse relationship.…”
Section: Bnp and T3 Treatment Of Hfmentioning
confidence: 55%
“…Linear regression line is indicated. Pinelli et al, 2007;Mayer et al, 2008;Pfister et al, 2010;Du et al, 2012;Brozaitiene et al, 2016;She et al, 2018;Sato et al, 2019). Based on this observation, we explored the utility of BNP as a measure of cardiac tissue TH function using animal models of hypothyroidism and MI.…”
Section: T3 Bnp α-Mhc Relationshipmentioning
confidence: 95%
“…All subjects were enrolled from the respiratory and critical care department of the First Affiliated Hospital of Xi'an Jiaotong University, China, from September 2017 to September 2018. Written informed consent was obtained from all subjects according to the Declaration of Helsinki, and the study was approved by the ethics committee of Xi'an Jiaotong University [11][12][13] . We included a cohort of 13 young adults and 36 healthy controls between the ages of 18 and 30 years old.…”
Section: Methodsmentioning
confidence: 99%
“…The patients were treated on an inpatient basis. Demographic and biochemical information was obtained as previously described [12][13][14] .…”
Section: Methodsmentioning
confidence: 99%
“…Demographic and biochemical information was obtained as previously described [13][14][15] Serum sample preparation Serum samples were collected from IHD, ICM and control patients after coronary angiography. Venous blood was withdrawn the next morning after overnight fast and immediately centrifuged at 3000 rpm for 10min at 4°C.…”
Section: Study Design and Populationmentioning
confidence: 99%